Control of two-spotted spider mite, Tetranychus urticae, on strawberry by integrating with cyetpyrafen and Phytoseiulus persimilis - Shan Zhao; Qiuyu Zhao; Xiaoyan Dai; Bing Lv; Ruijuan Wang; Zhenjuan Yin; Feng Zhang; Yan Liu; Long Su; Hao Chen; Li Zheng; Hongmei Li; et al. (CABI Agriculture and Bioscience)
Abstract The two-spotted spider mite (TSSM, Tetranychus urticae Koch) is a significant agricultural pest, particularly in strawberries. Management of TSSM has traditionally relied on synthetic acaricides, but to mitigate dependency on these chemicals, the control of TSSM on strawberry is often combined with biological control measures and chemical control strategies. The predatory mite, Phytoseiulus persimilis, is a promising biological control agent, preying on all TSSM developmental stages. In this study, we examined the toxicity of six common acaricides on TSSM and P. persimilis, and cyetpyrafen was selected due to its highest relative toxicity value. Then, we examined the compatibility of cyetpyrafen with P. persimilis for TSSM management on strawberries. The results suggested that cyetpyrafen revealed no substantial differences in prey consumption or longevity when compared to the control, though minor effects on the development durations of protonymphs and deutonymphs were noted in the subsequent generation. Additionally, cyetpyrafen's toxicity on key pollinators, such as Apis mellifera and Bombus terrestris, was found to be low. Thus, an integrated strategy combining cyetpyrafen (0.83 mg/L) with P. persimilis (predator–prey ratio of 1:30) was examined under laboratory and field conditions. Laboratory trials demonstrated a reduction in mites per leaf from 32.72 to 14.50 within 3 days, correlating to a 70.23% control efficiency. This efficacy increased to 96.04% by day 9 and was sustained until the experiment concluded on day 27. Field trials similarly showed a reduction in TSSM from 53.93 to 9.63 mites/leaf by day 6, achieving an 83.64% control efficiency, and culminated in a 98.46% reduction by day 10. These findings suggested that an integrated approach utilizing cyetpyrafen in conjunction with P. persimilis can be an effective alternative for TSSM management on strawberry plants.